2017
DOI: 10.15273/gree.2017.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Mining and the Sustainable Development Goals: A Systematic Literature Review

Abstract: 193 United Nations members are signatories of the 17 Sustainable Development Goals (SDGs). Even though it does not make it legally binding to the country members, the SDGs establishment incites national and managerial frameworks to achieve the SDGs. The mining industry inserts itself in this context by its global presence and frequent location within ecologically sensitive and less developed areas. This paper aims to consolidate the state of academic research on mining, sustainability and sustainable developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
0
9
1
2
Order By: Relevance
“…The LCS group shows more relationships between works. The study by Mesquita et al showed The LCS graph has more relations between works than the GCS graphs (Mesquita et al, 2017). The work of Nandiyanto (node 40) is an authority article and is used by other research as a theoretical basis in research on publications of chemistry and materials in universities.…”
Section: Science Mappingmentioning
confidence: 99%
“…The LCS group shows more relationships between works. The study by Mesquita et al showed The LCS graph has more relations between works than the GCS graphs (Mesquita et al, 2017). The work of Nandiyanto (node 40) is an authority article and is used by other research as a theoretical basis in research on publications of chemistry and materials in universities.…”
Section: Science Mappingmentioning
confidence: 99%
“…According to the imperative analysis of [33] and [34] Mining, processes have the ability to affect a wide range of environmental entities. They are of interest to a diverse range of stakeholder clusters, so there is plenty of room for the industry to become more sustainable.…”
Section: Sustainable Development In the Context Of Miningmentioning
confidence: 99%
“…A review of studies on sustainable development in mining may be found in (Asr et al, 2019;Gorman & Dzombak, 2018). Limited researches are about quantifying the sustainable development attributes (Amirshenava & Osanloo, 2019;Fernandes de et al, 2017). In addition, the limited research that addresses all three principles of sustainable development in mining is not about determining underground mine layout.…”
Section: Literature Reviewmentioning
confidence: 99%